ROOT GROWTH AND DISTRIBUTION OF THREE SUGARCANE CULTIVARS, IN RATOON CROP, IN TWO SOIL TYPES, IN RHIZOTRON. I. USE OF WinRHIZO - Ido, Oswaldo Teruyo; Daros, Edelclaiton; Zambon, José Luis Camargo; Weber, Heroldo; Buso, Pedro Henrique de Medeiros; Oliveira, Ricardo Augusto de (Scientia Agraria, 2006)
The present work had as objective to evaluate the growth and the distribution of the root system, in the first ratoon cropcycle, of three sugarcane cultivars, in two substratum types (Loamy and Sandy), in rhizotron conditions. The research was accomplishedin the Experimental Station of Paranavaí/SCA/UFPR, of June of 2000 to July of 2001. The root length and the distribution were analyzed through the methodology of samples volumetric as associated to the readings of WinRHIZO. The substratum influenced the root growth of the cultivars. With relationship to the quantitative distribution of the length total of the roots RB835486 and SP80-1842 presented better performances in the loamy substratum, while the cultivar RB855536 showed larger amount of the root system in the sandy substratum. The rhizotron is a viable structure for the study of the root system of the ratoon crop.